SIFAT FISIK DAN MEKANIK BATANG KELAPA SAWIT (Elaeis guineensis Jacq) BERDASARKAN PADA POSISI KETINGGIAN BATANG - dy, En; Diba, Farah; hati, Mufli (JURNAL HUTAN LESTARI, 2014)
The research aims to determine the physical properties (moisture content, density and dimensional stability) and mechanical properties (modulus of elasticity, modulus of rupture, and modulus of crush stiffness) of Elaeis guineensis Jacq based on the position the trunk). The design used in the study was a completely randomized design (CRD) with 3 replications and the factor is the position of the stem height (low, middle, and top) of oil palm (Elaeis guineesis Jacq). The results showed that height position have significant value to moisture content, MOR and MCS, but did not significantly affect the value of density, dimensional stability and MOE. The moisture content value was range from 38,49 % - 101,07 %, and the density value was range from 0,46 gr/cm3 – 0,62 gr/cm3, meanwhile the dimensional stability value was range from 11,54 % - 19,84 %. The modulus of elasticity value was range from 4456,77 gr/cm2 – 10062,40 gr/cm2, and modulus of rupture value was range from 108,20 gr/cm2 – 354,47 gr/cm2, meanwhile the modulus of crush stiffness value was range from 16,56 gr/cm2 – 69,96 gr/cm2. The research concluded that oil palm trunk in the low position have physical and mechanical properties better than in the middle and top, and enroll in class V of strongness and suitable for use as raw material for particle board or other composite products. Keywords : oil palm trunk, physical, mechanical properties, Elaeis guineensis Jacq